1987
DOI: 10.1037/0096-1523.13.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-manual pursuit tracking of human two-dimensional movements.

Abstract: We investigated visuo-manual pursuit tracking in 10 adult subjects. The main features of the experi ments were as follows: (a) The targets to be pursued were planar (two-dimensional) trajectories. (b) Targets were based on actual human hand movements. A set of five different extemporaneous movements (scribbles) were rear-projected on a digitizing table with their original timescale. (c) Targets were presented both as originally recorded (Condition N) and after a numerical manipulation that made the tangential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 53 publications
8
46
2
Order By: Relevance
“…It thus seems to be possible to execute movements in which velocity and geometry do not match according to the 2/3 power law. This finding is in contrast with previous studies on manual tracking of predictable (Viviani and Mounoud 1990) and unpredictable twodimensional movements (Viviani et al 1987) and in a study in which participants had to reproduce a movement that was imposed on the right arm with the left arm (Viviani et al 1997). These studies demonstrated that it is nearly impossible to produce movements violating the 2/3 power law.…”
Section: Progress In Motor Learningcontrasting
confidence: 55%
See 1 more Smart Citation
“…It thus seems to be possible to execute movements in which velocity and geometry do not match according to the 2/3 power law. This finding is in contrast with previous studies on manual tracking of predictable (Viviani and Mounoud 1990) and unpredictable twodimensional movements (Viviani et al 1987) and in a study in which participants had to reproduce a movement that was imposed on the right arm with the left arm (Viviani et al 1997). These studies demonstrated that it is nearly impossible to produce movements violating the 2/3 power law.…”
Section: Progress In Motor Learningcontrasting
confidence: 55%
“…In contrast to previous studies (Viviani 2002;Viviani and Mounoud 1990;Viviani et al 1987) but similar to findings of Wann et al (1988), the typical curvature-velocity relation as predicted by the 2/3 power law seems to be altered after motor training.…”
Section: Introductioncontrasting
confidence: 56%
“…This observation has been formalized as the "two-thirds power law" relating speed and curvature (Lacquaniti et al 1983;Viviani and Cenzato 1985). It holds even when subjects track moving targets; performance is degraded if the target motion does not conform to this relation (de'Sperati and Viviani 1997;Viviani et al 1987). In fact, this covariation between speed and curvature is maintained qualitatively when subjects trace unknown and unseen curvilinear closed contours (unpublished observations).…”
Section: S E N S O R Y C U E S I N H a P T I C S E N S I N Gmentioning
confidence: 94%
“…It has been suggested (Hoffman & Flinchbaugh, 1982) that these motor schemes are instrumental for providing a veridical three-dimensional (3D) interpretation of the retinal images. Moreover, further evidence of a motor component in the interpretation of visual information has come from the results of two experiments on visuomanual pursuit tracking (Viviani, Campadelli, & Mounoud, 1987;Viviani & Mounoud, 1990), which show that it is virtually impossible to accurately pursue two-dimensional (2D) targets that do not comply with certain regularities that characterize biological motions.…”
mentioning
confidence: 99%